Whither Just Transition? A Case Study of Energy Transition Mechanism (ETM) Country Platform in Indonesia - Aldi Haydar Mulia; Sekarini Wukirasih; Widhi Hanantyo Suryadinata (Institute of International Studies, 2023)
Without a coordinated and effective global energy transition action plan, numerous projects and aid given by the Global North states dominated today's energy transition scheme–particularly for many Global South states. One is Energy Transition Mechanism (ETM), which claims to actualise just transition through its platform recently launched in Indonesia. It promises to improve societal participation, address socio-economic issues, and gives its recipients an affordable and sustainable path to a just transition. The latter focuses on early coal retirement, which is rampant in Indonesia. Despite its relatively novel focus on just transition, ETM fails to live up to its